Duration of preoperative clear fluid fasting and peripheral intravenous catheterization in children: A single‐center observational cohort study of 9693 patients. Issue 2 (19th December 2019) - Galvez, Jorge A.; Wu, Lezhou; Simpao, Allan F.; Tan, Jonathan; Muhly, Wallis; Masino, Aaron; Sutherland, Tori; Wasey, Jack O.; Nelson, Olivia; Lin, Elaina; Fiadjoe, John E.; Stricker, Paul
Abstract: Background: Children routinely undergo inhalational induction of general anesthesia. Intravenous line placement typically occurs after induction of anesthesia and can be challenging, particularly in infants and young children. Aims: We conducted a retrospective observational study to determine whether there was an association between clear liquid fasting time and the number of peripheral intravenous catheter insertion attempts in anesthetized children. The secondary aim was to identify factors associated with multiple attempts to insert intravenous lines. Methods: After institutional research board approval, we retrieved a data set of all children between 0 months and 18 years who received general anesthesia at our hospital between January 1, 2016, and September 30, 2017. Data included age, gender, weight, race, ASA status, gestational age, number of peripheral intravenous catheter insertion attempts, any assistive device for insertion, and insertion site. Inclusion criteria were mask induction, ASA status 1 or 2, nonemergency, ambulatory surgical procedures, and placement of a single intravenous line during the anesthetic. Results: A total of 9693 patients were included in the study. Of which 8869 patients required one insertion attempt and 824 underwent multiple insertion attempts. 50% of patients in the single insertion attempt group had clear liquid fasting time <6.9 hours compared to 51.8% of patients requiring multiple attempts. Logistic regression model adjusted for age, ASA status, gender, and BMI did not find an association between duration of clear liquid fasting time and rate of multiple insertion attempts for intravenous catheters (OR: 0.99, 95% CI: 0.98‐1.01, P  = .47). Conclusion: Clear liquid fasting time was not associated with multiple insertion attempts for intravenous line insertion in children receiving general anesthesia. Factors such as patient age, ethnicity, time of day of induction of anesthesia, and American Society of Anesthesiologists Physical Status classification show a greater association with the risk of multiple intravenous line insertion attempts.